No difference in intestinal strontium absorption after an oral or an intravenous 1,25(OH)2D3 bolus in normal subjects - Bianchi, Maria L.; Ardissino, Gianluigi; Schmitt, Claus P.; Daccó, V.; Barletta, L.; Claris‐Appiani, A.; Mehls, Otto (Journal of bone and mineral research, 1999)
It has been suggested that 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) stimulates intestinal calcium absorption less via the intravenous (iv) than the oral route, because the first avoids direct contact of the drug with the enterocytes. However, no study has addressed the issue directly. This investigation was designed to measure the effect of a single oral or iv dose of 1,25(OH)2D3 on calcium absorption, using stable strontium (Sr) as a surrogate for calcium, and measuring the Sr fractional absorbed dose (FAD%) over 240 minutes after Sr administration. In 10 healthy volunteers, five tests were performed in a cross-over design, with a wash-out period between two consecutive tests: Sr absorption without 1,25(OH)2D3 (test A); Sr absorption immediately after either oral (test B) or iv (test C) 1,25(OH)2D3 (1.5 μg/m2 of body surface area [BSA]); Sr absorption (24 hr after either oral (test D) or iv (test E) 1,25(OH)2D3 (1.5 μg/m2 BSA). The concurrent administration of 1,25(OH)2D3 and Sr (tests B and C) did not significantly change the area under the Sr FAD%-time curve with respect to test A (test A: 4090 ± 345; test B: 4510 ± 345; test C: 4210 ± 345), whereas Sr absorption was significantly increased (p < 0.001) when Sr was given 24 hr after either oral or iv 1,25(OH)2D3 (test D: 5710 ± 345; test E: 5510 ± 345). It was concluded that 1,25(OH)2D3 is likely to influence calcium absorption significantly only via its genomic effect, independent of its administration route.
First published: 02 December 2009
Im Titel sind die Ziffern "2" und "3" nach (OH) tiefgestellt
Gesehen am 14.01.2021